An impact of cross-border M&A deals on economic growth of the Russian Federation - V. K. Bataeva (Путеводитель предпринимателя)
This paper analyses the dependence of the cross–border M&A deals on economic growth of Russia using correlation regression analysis. Data for the value and quantity of M&A deals on the Russian market and macroeconomic indicators of growth was used as empirical base. The data period is from 2010 till 2019. The main hypothesis of proportion of economic growth from the quantity of cross–border M&A deals has confirmed, although it may be concluded that the value of cross–border M&A deals doesn’t influence on the economic growth of Russia.